Development of vocational science learning devices to improve project based soft skills - Khamdun, Khamdun; Suparmi, Suparmi; Maridi, Maridi; Rusilowati, Ani (Linguistics and Culture Review, 2021)
This study aims to produce a Vocational High School Natural Science learning tool to improve project-based soft skills that are valid, practical and effective in developing student soft skills. The method used is Research and Development (R&D) referring to the 4-D model suggested by Thiagarajan with the stages namely define, design, develop, and disseminate. The population in this study were students of class XI in the machine technology group of SMK Negeri 2 Kudus in the academic year 2019/2020 (N = 61). The sample in the study were students of class XI with the expertise of machine technology (n = 34) who were taken by random sampling technique. The data were collected using the device validation sheet, the implementation observation sheet, the teacher’s response questionnaire and the student response questionnaire. Data about the validity and practicality of the device in developing learning tools to improve project-based soft skills were analyzed using the right-hand t-test with ? of 0.05.